(untitled) (Archives of Mechanics - Test, 2005)
Managing Editor of the Archives of Mechanics (1999-2005) J. Joachim Telega was born in Przyszowice in Poland on March 24, 1943. He received two Master’s degrees: in 1968 at the Technological Department of the Silesian University in Gliwice and in 1970 at the Mathematics, Physics and Chemistry Department of the same University. He had been working there until the 1977 and received his Ph.D. degree in 1972. Since 1977 until the last days of his life he had a permanent position at the Institute of Fundamental Technological Research (IFTR), Polish Academy of Sciences in Warsaw, becoming full Professor here in 1999. Since 2001 he was the head of the Division of Variational Methods and Biomechanics of the Department of Mechanics of Materials and Biomechanics.